FAKTOR-FAKTOR YANG MENDORONG PEMANFAATAN JURNAL ELEKTRONIK DI UNIVERSITAS NEGERI YOGYAKARTA - Dwi Surtiawan; Waliantoro; Rahman Anto Wibowo; Anwar Ardianto (Pustakaloka, 2025)
The purpose of this study is to identify the factors influencing the utilisation of electronic journals subscribed to by Universitas Negeri Yogyakarta (UNY), with the aim of optimising their use and ensuring that institutional investments generate commensurate benefits. This study employed a quantitative research design using a survey method. The population consists of all UNY students, from diploma 4 to doctoral levels. The total number of UNY students is approximately 57,289. The sample was determined using proportionate stratified random sampling, in which respondents were selected randomly from proportionally defined strata of the population. This technique was used because the population was spread across several groups. The sample size was determined using Slovin’s formula, resulting in 156 respondents with a 10% margin of error. Data collection techniques included questionnaires, interviews, literature studies, and direct observation. The information system evaluation framework employed in this study was the Weber Model, which comprises eight evaluation parameters. The eight parameters of the Weber Model consist of: (1) information quality, (2) system quality, (3) individual impact, (4) perceived ease of use, (5) computer proficiency, (6) system usability, (7) system usefulness, and (8) information system satisfaction. The results indicate that all eight proposed factors have a statistically significant effect on the utilisation of the electronic journal information system at UNY.